Conversion coefficients for the estimation of effective dose in cone-beam CT - Kim, Dong-Soo (Korean Academy of Oral and Maxillofacial Radiology, 2014)
PURPOSE: To determine the conversion coefficients (CCs) from the dose-area product (DAP) value to effective dose in cone-beam CT. MATERIALS AND METHODS: A CBCT scanner with four fields of view (FOV) was used. Using two exposure settings of the adult standard and low dose exposure, DAP values were measured with a DAP meter in C mode (200mm×179 mm), P mode (154 mm×154 mm), I mode (102 mm×102 mm), and D mode (51 mm×51 mm). The effective doses were also investigated at each mode using an adult male head and neck phantom and thermoluminescent chips. Linear regressive analysis of the DAP and effective dose values was used to calculate the CCs for each CBCT examination. RESULTS: For the C mode, the P mode at the maxilla, and the P mode at the mandible, the CCs were 0.049 µSv/mGycm(2), 0.067 µSv/mGycm(2), and 0.064 µSv/mGycm(2), respectively. For the I mode, the CCs at the maxilla and mandible were 0.076 µSv/mGycm(2) and 0.095 µSv/mGycm(2), respectively. For the D mode at the maxillary incisors, molars, and mandibular molars, the CCs were 0.038 µSv/mGycm(2), 0.041 µSv/mGycm(2), and 0.146 µSv/mGycm(2), respectively. CONCLUSION: The CCs in one CBCT device with fixed 80 kV ranged from 0.038 µSv/mGycm(2) to 0.146 µSv/mGycm(2) according to the imaging modes and irradiated region and were highest for the D mode at the mandibular molar.